Optimalisasi Komunikasi Digital UMKM di Bojonggede: Strategi Chat Konsumen, Katalog Produk dan Presentasi Efektif - Bachtiar, Alfan; Barizki, Rezzi Nanda; Alamsyah, Alamsyah; Awaludin, Dipa Teruna; Sitinah, Sitinah (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Bojonggede, Bogor Regency, in strategically utilizing digital communication tools. The core training activities focused on three key areas: customer communication through chat platforms, the development of visually appealing product catalogs, and effective product presentation techniques. Employing a participatory approach, the participants were introduced to theoretical concepts and hands-on practices to refine their digital communication skills aligned with current market dynamics. The evaluation results indicate that the training significantly impacted the participants’ ability to engage with customers professionally and promote their products in a more structured and compelling manner. This program is expected to serve as a replicable model for digital communication empowerment among other MSME communities in surrounding regions